Systematic review and meta-analysis of magnetic resonance imaging in the diagnosis of pulmonary embolism - Chuan-Hua Yang; Miao Yu; Deng-Chao Wang (BMC Medical Imaging)
Abstract Background Pulmonary embolism is a significant clinical challenge with high mortality risk. Computed Tomography Pulmonary Angiography (CTPA) is the gold standard for diagnosis but involves radiation risks. Magnetic Resonance Imaging (MRI) offers a radiation-free alternative, yet its adoption is hindered by inconsistent validation of its diagnostic accuracy. This study systematically assesses MRI’s efficacy in diagnosing pulmonary embolism, incorporating a broad range of literature to ensure comprehensive analysis. Methods Relevant studies on the diagnostic use of MRI for pulmonary embolism were collected through computer searches of PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, and China Biology Medicine disc (CBM) databases up to May 12, 2024. Literature was screened based on inclusion and exclusion criteria, data extracted, and study quality assessed according to Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) standards. Data analysis was performed using Stata (versions 17.0 and 14.0) and Meta-Disc 1.4 software. Stata software was used to calculate pooled sensitivity, pooled specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio, and to plot forest plots, hierarchical summary receiver operating characteristic (HSROC) curves, and summary receiver operating characteristic (SROC) curves. The area under the SROC curve (AUC) was calculated, and publication bias was assessed through Deek’s funnel plot, Egger’s test, and Begg’s test. Results Eighteen articles involving 1,264 participants were included. The meta-analysis showed that MRI for the diagnosis of pulmonary embolism had a pooled sensitivity of 0.89 (95% CI: 0.79–0.94) and a specificity of 0.94 (95% CI: 0.89–0.97). The pooled positive likelihood ratio was 14.6 (95% CI: 8.0-26.7) and the negative likelihood ratio was 0.12 (95% CI: 0.06–0.23). The diagnostic odds ratio was 121 (95% CI: 49–299). The AUC of the SROC was 0.97. Deek’s funnel plot suggested potential publication bias in the studies included. Conclusion MRI exhibits high sensitivity and specificity in the diagnosis of pulmonary embolism, demonstrating excellent diagnostic efficacy. Despite potential publication bias, MRI continues to show strong potential for clinical application.